Religions et classes sociales - Favier, Anthony; Fer, Yannick; Galonnier, Juliette; Perrin-Heredia, Ana (Sociétés, Espaces, Temps, 2023)
Reviewing the research in recent decades on the links between religions and social classes amounts in part to documenting an absence. However, this eclipse is relatively recent because this topic has long been a classic in the social sciences. Has the articulation between religious and class affiliations become so discreet or, on the contrary, so obvious that it now flies under our radars? The eleven qualitative surveys gathered in this volume reopen this field of investigation. They question our ways of seeing (or not seeing) these links and invite us to further the analysis beyond apparent elective affinities, by looking at the overlaps, the misalignments and the tensions between religions and social classes. Through immersion in a diversity of historical contexts, geographical areas, religious traditions and social groups, the contributions illustrate the topicality of these questions and their relevance for understanding the construction of social boundaries and the reproduction of inequalities. With its fine empirical analyses and rigorous theoretical framework, this book is a must-read for students and researchers in the social sciences, as well as for all professionals who deal with issues related to religion and class in their work.